Disulfide bond and free radical copolymerization endow TPU with reversible cross-linking properties - Wenxin Gan; Hanyu Xue; Hongyi Lin; Renjin Gao; Yuchi Zhang; Liwei Wang; Jiuping Rao (eXPRESS Polymer Letters)
Cross-linking frequently enhanced the mechanical properties of linear polymeric materials; however, it also resulted in the transition from thermoplastic to thermosetting materials, which posed issues from an environmental perspective. Thermoplastic polyurethane (TPU) elastomers were extensively applied across various industries. To improve the mechanical properties of TPU while preserving its environmental benefits, this study integrated radical copolymerization technology to develop a reversible crosslinked TPU. Specifically, the linear polyurethane molecular chains were crosslinked using diallyl disulfide (DADS) as a functional cross-linking monomer. Through radical copolymerization reactions, reversible crosslinks formed from disulfide bonds were created between the linear polyurethane molecular chains, yielding a self-healing reversible crosslinked thermoplastic polyurethane (DSTPU). The study showed that DSTPU could self-heal and dissolve under UV light and alkaline N,N-dimethylformamide (DMF) conditions, achieving 82.2% self-healing efficiency at 3 phr DADS. It dissolved into fine particles in alkaline DMF. Disulfide bonds in DSTPU enhanced cross-linking, boosting 19% oxygen permeability, thermal conductivity (0.218 W/(m·K)), and mechanical properties like tensile stress (11.18 MPa), force (134.13 N), and elongation (548%). These bonds also enhanced aging resistance, cutting ΔYI to 6.0%.